Social studies students’ knowledge, attitude and practice of concepts of sustainable development in Ondo City, Nigeria - Omoniyi Timilehin Olayinka (International Journal of Financial, Accounting, and Management, 2020)
Abstract Purpose: The study investigates Social Studies’ students’ knowledge, attitude, and practices of concepts of sustainable development in selected junior secondary school in Ondo city, Nigeria. Research Methodology: The survey was conducted involving five hundred (540) students from ten (18) junior secondary schools. A self-constructed questionnaire titled “Social studies’ students knowledge, attitude, and practices of concepts of sustainable development in selected junior secondary school in Ondo state QSSSKAPCSD Cronbach alpha Reliability co-efficient of; KSDC: 0.70; PSDC: 0.73, and ASDC: 0.71 respectively was used. Three research questions were answered using simple percentage, mean (x) and standard deviation. Result: The result shows Social Studies’ students’ level of knowledge, attitude and practices of sustainable development concepts is at an appreciable high level. The study recommended full implementation of various UNESCO’s plan on sustainable development goals by all countries in the world. Limitation: Sample size and area of coverage was the limitation of the study and this was due to the constraint of time and finance. Further studies should carry out an inferential statistics to analyse the variables. Contribution: The study assessed students’ level of knowledge, attitude and practices of sustainable development concepts in Social Studies. Keywords: Sustainable development, Knowledge, Attitude, Practice